Tabuh Sinom Ladrang Training at Seka Gong Children Jaya Kumara Banjar Busana, Abiansemal | Pelatihan Tabuh Sinom Ladrang Pada Seka Gong Anak-Anak Jaya Kumara Banjar Busana, Abiansemal - I Putu Dony Suryawan; Ni Putu Hartini (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
KKNT activities include the preparation stage, teaching practice, and implementation. The results achieved from the performance of the individual program are to provide changes in the learning process, especially in the field of expertise of the active and exciting karawitan study program, as well as train students' process skills in drumming, especially the practice of tabuh gending as an example of Sinom Ladrang gending. Individual programs can run well and benefit the personal progress of constituents, students, lecturers, and institutions in supporting the process of practicum activities in the field for now and in the future. Apart from being a vehicle for student training and learning, the KKNT program is also an effort by the Indonesian Institute of Arts Denpasar to contribute to transforming educational values in society. The hope is not only as an additional insight provided by the village area where they contribute but also as a transfer of value. It is hoped that the students of the Thematic Real Work Lecture of the Indonesian Institute of the Arts Denpasar 2023 will be able to make changes to advance Indonesian education in the arts.